Robust GNSS/INS hybrid integration based on multi-state validation of GNSS measurements - Wang, Shan; Huang, Haotang; Tang, Fangzhou; Zhu, Bocheng (Frontiers in Physics, 2025)
The Global Navigation Satellite System (GNSS) is generally combined with the Inertial Navigation System (INS) to deliver reliable and high-performance navigation, particularly in scenarios where GNSS signals may be compromised. This integration leverages the inherent strengths of both systems to ensure continuous and accurate positioning. To enhance the robustness and accuracy of navigation systems in challenging environments, this paper proposes a novel hybrid integration (HI) approach for GNSS/INS fusion. The system incorporates a Multiple State Inspection of GNSS Observations (MSI-GO) mechanism, which dynamically selects the optimal integration mode based on the number of visible satellites (NoS) and position dilution of precision (PDoP), thereby achieving a balance between positioning performance and computational efficiency. Simulation results using an open dataset demonstrate that, compared to traditional loosely coupled (LC) and tightly coupled (TC) methods, the HI scheme improves positioning accuracy by approximately 5% while reducing computational complexity by around 25%. This validates the proposed approach as both stable and resource-efficient, with strong applicability in real-world navigation scenarios.